Machine learning of genomic features in organotropic metastases stratifies progression risk of primary tumors - Biaobin Jiang (Nature Portfolio, 2021)
The location and timing of metastasis are still fundamentally unpredictable. Here the authors present the Metastatic Network model, a machine learning framework that integrates clinical data and DNA alterations to predict the risk of metastasis to specific organs as well as clinical outcomes